Pengaruh Tingkat Kesehatan Keuangan Terhadap Pendapatan Kontribusi Dana Tabarru Pada Perusahaan Asuransi syariah - Lubis, Siti Nurhaliza; Lubis, Fauzi Arif; Nasution, Juliana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This researcher can aim to determine the effect on capital ratio-based RBC which is on the income contribution to Sharia Life Insurance companies listed on the Indonesia Stock Exchange BEI 2016-2021. By using this research method, it can be used with its quantitative approach by using data analysis which is assisted by the SPSS 2020 application. This research can be carried out with general insurance companies registered on the IDX where there is a collection of data in this study from sources of insurance company financial reports, this can go through the website www.idx.co.id the results of the regression analysis, this can be concluded in a partial way on the RBC risk based capital variable which can be influenced by the significant level of contribution income variables. And the existence of a significant value of 0.002 <0.05 or a t-count value of 3.513 > t-table 2.048 can be interpreted that H1 accepts and H0 rejects, so that it can be partially interpreted that the variable Level of Financial Soundness X can be influenced by its significant value in the Contribution Income variable Y. The following results mean that the Summary modeling can be obtained with an r (square) value of 0.281 with 28.1%. This can be interpreted that the effect of the level of financial soundness is in the contribution of income to Islamic insurance companies listed on the Indonesia Stock Exchange IDX 2016 – 2021 of 28.1% which remains with 71.9% and this can be influenced by variables that are therefore not other research on research This .